Respostas

2013-11-23T12:51:09-02:00
 (u+v) + w= u+(v+w)
{(2,2) + (3,3) } + (4,4)= (2,2) + {(3,3) + (4,4)
(5,5) + (4,4) = (2,2) + {(7,7)} (9,9) = (9,9) Quer dizer que tanto faz (u+v) + w ou u+(v+w)

V= A+u
 4,4 = 2,2 + 2,2 4,4 = 4,4 C=B+v 5,5 = 1,1 + 4,4 5,5 = 5,5 D=C+w 6,6 =5,5 + 1,1 6,6 = 6,6
1 5 1
2013-11-23T13:38:53-02:00
Sejam u = B - A, v = C - B, w = D-C
Assim,
(u+v) + w = [(B-A)+(C-B)] + (D-C)=[ C - A ] + ( D - C) = D - A
Por outro lado,
u + (v+w) = (B-A)+[(C-B)+(D-C)] = (B - A) + [D - B] = D - A
Logo,
(u+v)+w=u+(v+w)
c.q.d
1 5 1
amigo ajudo mt
da um click no azulzinho hehehe